Evidence in oyster of a plasma extracellular superoxide dismutase which binds LPS - Gonzalez, Marcelo; Romestand, Bernard; Fievet, Julie; Huvet, Arnaud; Lebart, M; Gueguen, Yannick; Bachere, Evelyne (Biochemical and Biophysical Research Communications, 2005)
We have characterized in the oyster Crassostrea gigas an extracellular superoxide dismutase (Cg-EcSOD) which appears to bind lipopolysaccharides (LPS). The protein has been purified from the oyster plasma and identified as a Cu/ZnSOD according to its N-terminal sequencing and biological activity. Cg-EcSOD expression and synthesis are restricted to hemocytes as revealed by in situ hybridization and immunocytochemistry. Cg-EcSOD-expressing hemocytes were seen in blood circulation, in connective tissues, and closely associated to endothelium blood vessels. Cg-EcSOD presents in its amino acid sequence a LPS-binding motif found in the endotoxin receptor CD14 and we show that the protein displays an affinity to Escherichia coli bacteria and with LPS and Lipid A. Additionally, an RGD motif known to be implicated in the association to membrane integrin receptor is present in the amino acid sequence. The purified Cg-EcSOD was shown to bind to oyster hemocytes and to be immunocolocalized with a beta-integrin-like receptor. (c) 2005 Elsevier Inc. All rights reserved.